2012
DOI: 10.1007/s11517-012-0970-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalized clinical in-silico modeling of atrial anatomy and electrophysiology

Abstract: Computational atrial models aid the understanding of pathological mechanisms and therapeutic measures in basic research. The use of biophysical models in a clinical environment requires methods to personalize the anatomy and electrophysiology (EP). Strategies for the automation of model generation and for evaluation are needed. In this manuscript, the current efforts of clinical atrial modeling in the euHeart project are summarized within the context of recent publications in this field. Model-based segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…Biophysically detailed three-dimensional computational models have been developed for major parts of the heart [7,9], with several models accounting for various details of atrial electrophysiology and anatomy [8,9,[26][27][28][29]. Comprehensive review of such models can be found elsewhere [9].…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biophysically detailed three-dimensional computational models have been developed for major parts of the heart [7,9], with several models accounting for various details of atrial electrophysiology and anatomy [8,9,[26][27][28][29]. Comprehensive review of such models can be found elsewhere [9].…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…Fibre orientation has been included in atrial models manually based on anatomical observations [8,26,27] or semi-automatically based on known atrial activation patterns [28,29]. Besides, even the most recent atrial models [8,28,29] have not accounted for electrophysiological heterogeneity and anisotropy of the PV region, which are crucial in the genesis of AF [1][2][3][4][5]. Our three-dimensional model of the canine PV region overcomes such limitations and provides a missing link in the large-scale modelling of the entire threedimensional atria and heart.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…They also incorporated clinical knowledge about how cardiovascular disease disturbs the correct functioning of the heart at these levels. Atrial modeling is currently in a transition from the sole use in basic research to future clinical applications (Krueger et al 2013 ).…”
Section: Project Euheart For Personalized Management Of Heart Diseasementioning
confidence: 99%
“…2, 11.9 K nodes, average internodal distance of 2.0 mm). The latter was composed of several connected structures, manually added to the atrial chambers, with geometry and fiber orientation mimicking [30], [31].…”
Section: B Geometrical Modelmentioning
confidence: 99%
“…Our adaptive algorithm may favor the diffusion of patient-specific AF simulations [31] in the clinical setting by reducing computational costs and hardware requirements. For instance, thanks to the 90% decrease in workload, simulations could be accurately performed on nondedicated desktop computers in clinically acceptable times (1 h for 1 s simulation).…”
Section: B Clinical Implicationsmentioning
confidence: 99%